Effect of different levels of EDTA on phytoextraction of heavy metal and growth of Brassica juncea L. - Kamal, Mohab Amin; Perveen, Kahkashan; Khan, Faheema; Sayyed, R. Z.; Hock, Ong Ghim; Bhatt, Santosh Chandra; Singh, Jyoti; Qamar, Mohd Obaid (Frontiers in Microbiology, 2023)
To explore the probable function of EDTA in ameliorating heavy metal toxicity, we treated Brassica juncea L. seedlings with different concentrations of EDTA (0, 1.0, 2.0, 3.0, and 4.0 mM Kg -1 ) in heavy metal-polluted soil. In the absence of EDTA, B. juncea seedlings accrued heavy metals in their roots and shoots in a concentration-dependent manner. However, the highest biomass of plants (roots and shoots) was recorded with the application of 2 mM kg −1 EDTA. Moreover, high levels (above 3 mM kg -1 ) of EDTA concentration have reduced the biomass of plants (roots and shoots), photosynthetic area, and chlorophyll content. The effect of EDTA levels on photosynthetic pigments (chlorophyll a and b) revealed that with an increment in EDTA concentration, accumulation of heavy metals was also increased in the plant, subsequently decreasing the chlorophyll a and b concentration in the plant. Moreover, values of the phytoremediation factor were utilized to assess the accumulation capacity of heavy metals by B. juncea under EDTA treatments. TLF was found to be in the order Pb> Hg> Zn> and >Ni, while TF was found to be in the order Hg>Zn>Ni>Pb, and the best dose was 3 mM kg −1 EDTA for Hg and 4 mM kg -1 for Pb, Ni, and Zn. Furthermore, hyperaccumulation of heavy metals enhanced the generation of hydrogen peroxide (H2O2), superoxide anions (O2 •− ), and lipid peroxidation. It also interrupts mechanisms of the antioxidant defense system. Furthermore, heavy metal stress reduced plant growth, biomass, and chlorophyll (chl) content. These findings suggest that the exogenous addition of EDTA to the heavy metal-treated seedlings increases the bioavailability of heavy metals for phytoextraction and decreases heavy metal-induced oxidative injuries by restricting heavy metal uptake and components of their antioxidant defence systems.